Implementasi Aplikasi E-Peken dalam Upaya Pemberdayaan UMKM di Kota Surabaya Pasca Pandemi Covid-19 - Balqista Safia Haya; Kalvin Edo Wahyudi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to analyze and describe the implementation of the E-Peken Application in the City of Surabaya in an effort to empower MSMEs after the Covid-19 pandemic. This research uses qualitative research with a descriptive approach. This research data was collected through observation, interviews and documentation. The informants in this study consisted of 6 informants, namely 2 related agencies, 2 MSMEs and 2 ASN. Data validation was carried out through triangulation of sources, techniques and time and then analyzed through data analysis techniques, namely data collection, data presentation, drawing conclusions and data condensation. To find out the extent of the implementation of the E-Peken application in the city of Surabaya, this research uses the results of studies and research from the Harvard JFK School of Government, namely elements of success which include support, capacity and value. The results of observations and interviews with several informants show that the implementation of the E-Peken Application in the City of Surabaya in an effort to empower MSMEs is going well. In its implementation, there are still several problems with the infrastructure where several features in the E-Peken Application still need to be added and developed further. The Surabaya City Government, especially Diskominfo and Dinkopdag, as those responsible for the E-Peken Application, need to improve and develop the E-Peken Application so that it can run more effectively and efficiently so that users, especially MSMEs who use the E-Peken Application, get significant benefits.